2014
DOI: 10.1021/jp409844y
|View full text |Cite
|
Sign up to set email alerts
|

Gold Dimer Nanoantenna with Slanted Gap for Tunable LSPR and Improved SERS

Abstract: International audienceWe focus on improving the surface-enhanced Raman scattering (SERS) of dimer nanoantenna by tailoring the shape of the coupled nanoantennas extremities from rounded to straight or slanted ones. A numerical model based on the discrete dipole approximation method—taking into account periodicity, adhesion layer, and roughness—is first validated by comparison with localized surface plasmon resonance (LSPR) and SERS experiments on round-edged dimer nanoantennas and then used to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 75 publications
2
70
0
Order By: Relevance
“…For example, it has been demonstrated that dimers of gold nanorods with a slanted gap provides an improvement of the enhancement factor by 2 orders of magnitude compared to the rounded shape use in this paper. 79 Another example is given by the change of the adhesion layer (Cr or Ti) between the gold nanostructures and the dielectric substrate by an adhesion layer of (3-mercaptopropyl)-trimethoxysilane (MPTMS). In this case, the LSPR damping is decreased that induces an improvement of the SERS signal by a factor 10.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, it has been demonstrated that dimers of gold nanorods with a slanted gap provides an improvement of the enhancement factor by 2 orders of magnitude compared to the rounded shape use in this paper. 79 Another example is given by the change of the adhesion layer (Cr or Ti) between the gold nanostructures and the dielectric substrate by an adhesion layer of (3-mercaptopropyl)-trimethoxysilane (MPTMS). In this case, the LSPR damping is decreased that induces an improvement of the SERS signal by a factor 10.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For the unenhanced measurement, the total volume within which the analyte molecules are Raman scattered can be compared to a cylinder shape with height = 16 / and diameter 26,29,30 = 4 / where f is the focal length of the pump laser beam and d is the diameter of the unfocused beam. From this volume, the concentration of 1mM and Avogadro's number it was easy to estimate the number of molecules from the unenhanced measurement to be 8.48 × 10 15 . For a concentration of 10 mM the surface density µ of BPE can be estimated to be 31 1 × 10 -12 mol·mm -2 .…”
Section: Sers Measurementsmentioning
confidence: 99%
“…Although gold nanoparticles have lower enhancement values when compared to silver they are less prone to oxidation and show considerable robustness for use in plasmonic sensing 14 . Coupled pairs of nanoparticles such as dipoles 15 and bowties 16 have been widely used due to the formation of highly localized near-field enhancement (so called "hot spots") in these structures as well as to the ability to tune their resonant wavelength to that of the incident Raman wavelength 17,18 . Periodic arrangements of these nanoparticle pairs have high reproducibility and structural reliability and possess very high enhancement values due to the conversion of the irradiating energy at these hot spots 19 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Additionally, if the particle contains sharp tips, the lightning rod effect can occur. 5,11,12 The simplest model of a coupled plasmon system (nanoparticle aggregate) is a dimer in which two particles are closely packed. Understanding the mutual interaction between the aggregated nanoparticles is an up-to-date topic and the subject of much interest.…”
Section: Introductionmentioning
confidence: 99%